Spiritual well-being as variable intervening mindfulness dan life satisfaction - Dami, Zummy Anselmus; Tameon, Sance Mariana; Alexander, Ferdinant (Universitas Negeri Padang, 2018)
This research aimedÂ to know mindfulness significantly influenced spiritual well-being, to know the spiritual well-being significantly influenced life satisfaction, to know mindfulness significantly influenced life satisfaction, and to know the Spiritual well being mediated the influence of mindfulness toward life satisfaction. The subject in the research included 152 students of STAKN Kupang with 49 male students (32%) and 103 female students (68%), and were taken from four semesters with 50 first semesters student (33%), 34 third semester students (22%), 38 fifth semester students (25%), and 30 seventh semester students (20%). A quantitative research method was used with techniques such as regression analysis, path analysis, Sobel test and bootstrapping. The findings show that: (1) mindfulness significantly influenced the spiritual well-being; (2) spiritual well-being significantly influenced life satisfaction; (3) mindfulness did not influence life satisfaction; and (4) spiritual well-being mediated the influence of mindfulness toward life satisfaction.